An Investigation of Price Discovery in Informationally-Linked Markets: Equity Trading in Malaysia and Singapore - DING, David K. (Institutional Knowledge at Singapore Management University, 1999)
Using transactions data for the Kuala Lumpur Stock Exchange and the Stock Exchange of Singapore (SES) for a major Malaysian conglomerate, Sime Darby Berhad, and intraday exchange rate data, we investigate whether and to what extent each exchange contributes to price discovery. Results indicate that the price series are cointegrated. The raw data appear to indicate the presence of arbitrage opportunities, but none exist after taking exchange rate changes into account. Using the common long-memory factors of Gonzalo and Granger (1995, Journal of Business and Economic Statistics 13, 1-9), we show that while the majority of the price discovery (approximately 70%) occurs in the home country (Malaysia), the 26-32% of the price discovery attributable to the SES is statistically significant and exceeds Singapore's share of the trading volume. Further, we find evidence of strong error correction of Singapore prices to Malaysian prices, but only weak error correction of Malaysian prices to Singapore prices.